New Finds of Tokophrya wenzeli (Ciliophora, Suctorea) a Commensal of Water Mites (Acari, Hydracarina) and Redescription of a Species - Dovgal, I.V.; Zawal, A.; Pešić, V. (Вестник зоологии, 2012)
The article deals with investigations of suctorian species Tokophrya wenzeli Matthes et Stiebler, 1970 which was observed in waterbodies of Ukraine, Poland and Macedonia. New observations permit to precise the morphology of tentacles and show the variability of such sufficient characters of the species as morphology of basal plate, stalk and actinophores. The redescription of the species is also presented. Статья посвящена изучению суктории Tokophrya wenzeli Matthes et Stiebler, 1970, обнаруженной в водоемах Украины, Польши и Македонии. Новые данные позволили уточнить детали строения щупалец цилиаты, также оказалось, что важные для диагностики вида признаки, как строение базального диска, стебелька и актинофоров достаточно изменчивы. Приводится переописание вида.